Иллюзия любви: роман / Алисон Эшли - Эшли Алисон (Панорама романов о любви, 2010)
Экземпляры: ф.21 (20151127) / Инвентарный номер: 059987 / Цена: 30.00 / Авт.знак: Э 98 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)